THE INFLUENCE OF RETURN ON ASSET (ROA), NET PROFIT MARGIN (NPM), AND EARNINGS PER SHARE (EPS) ON STOCK PRICE IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Suriansyah Suriansyah (Indragiri Research Center (ingreat), 2023)
This study aims to determine the effect of variablesReturn On Asset (LONG),Net Profit Margin (NPM), andEarning Per Share (EPS) on share prices in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Data analysis techniques in this study used multiple linear regression analysis, classical assumption test, t test (partial), F test (simultaneous) and coefficient of determination test. Data processing in this study uses the SPSS V23 program. The results of this study indicate that the variable Return On Assets (ROA) has no significant effect on stock prices. Net Profit Margin (NPM) has no significant effect on stock prices. Earning Per Share (EPS) has a significant and influential effect on share prices in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. While simultaneously known thatReturn On Asset (LONG),Net Profit Margin (NPM), andEarning Per Share (EPS) has a significant influence on the stock prices of banking companies on the Indonesia Stock Exchange for the 2018-2020 period.